THE REGIONAL DIVIDE IN SMART CITIES IMPLEMENTATION A SOUTH-EAST COMPARATIVE ANALYSIS - Jaiswal, Amit (International Journal of Research -GRANTHAALAYAH, 2024)
India's Smart Cities Mission, launched in 2015, represents an ambitious attempt to modernize urban infrastructure across 100 cities. However, implementation has been highly uneven across regions. This paper examines the stark regional disparities between South and East India, analyzing 49 cities covering 3,564 projects worth Rs. 73,876 crore as of July 2023. South India demonstrates a completion rate of 78.8% compared to East India's 53.3%, representing a statistically significant gap of 25.5 percentage points (p<0.001). Through comparative analysis, this study identifies five key determinants of success: institutional capacity of state governments and urban local bodies, political stability and continuity, historical infrastructure investment patterns, project design and scale optimization, and fiscal autonomy and resource mobilization capabilities. The findings reveal that Karnataka (89.2% completion) and Tamil Nadu (84.3%) lead South India through strong state-level coordination, while Northeast states in East India face severe capacity constraints with completion rates as low as 11.8% (Shillong). This research contributes to understanding federal urban policy implementation in India and provides evidence-based policy recommendations for bridging regional disparities. The study has significant implications for the design of future national urban development programs and highlights the critical role of state capacity in determining implementation outcomes.